Política econômica e desenvolvimento humano e social: uma aproximação inaugural entre o direito e a economia - Stephanie Linhares Sales de Carvalho (2022)
The Constitution of the Federative Republic of Brazil of 1988 (CR/1988) established a Democratic State based on sovereignty, citizenship, dignity of the human being, social values of work, free initiative and political pluralism, in order to ensure social and individual rights, well-being and equality. The fundamental objective of the Republic, in order to achieve the proposed society project, was the construction of a free, just and solidary society, without poverty, marginalization, inequalities or distinction and national development. The constitutionally defined role for the Brazilian State is, therefore, that of an agent guaranteeing constitutional provisions, including fundamental and social rights, also established by normative and regulating state action of economic activity. Focused on human aspects and on supervision, incentive and state planning, the CR/1988 fits into the new constitutionalism, predominant from the second post-war period on, marked by its leading character, with an active State which brings Moral Right closer to positive values and principles. This dissertation is based on such premises to question whether the development constitutionally established as an objective of the Republic of Brazil is ensured by the adoption of neoliberal economic policies, such as deregulations, privatizations and liberalizations carried out since the 1990s. To test the hypothesis that neoliberal foundations are inconsistent with the CR/1988 because they weaken constitutionally determined state action, impairing development, variables such as: the meaning of development, understood as a condition of achieving the other objectives of Brazil and in its human perspective, analyzed the attributions of the Brazilian State according to the par-adigm of the Democratic State of Law and the effects of using neoliberal economic policies as a means for achieving the intended transformation of the social reality.